ANALISIS BAHASA HUKUM TERHADAP KRITIKAN DAN HINAAN MENURUT UNDANG UNDANG INFORMASI DAN TRANSAKSI PADA INSTAGRAM @aniesbaswedan - Diski Adlani; Kamaruzzaman Bustamam Ahmad; Novi Heryanti; Rispalman (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This study analyzes the differences between criticism and insults in the comments section of the Instagram account @aniesbaswedan and their application under the Electronic Information and Transactions Law (UU ITE), specifically Articles 27(3) and 28(2). The background of this study is reviewed in light of the increase in hate speech and impolite language on social media, which often blurs the line between freedom of expression and violations of the law. The method used in this study is a descriptive, qualitative, normative juridical approach, using the technique of observing and recording netizens’ comments on several posts by the @aniesbaswedan account. Data analysis was carried out using the interactive model Miles and Huberm, which includes data collection, reduction, presentation, and conclusion. The results of the study show that many comments contain insulting elements, such as harsh language, sarcasm, and personal accusations. In contrast, rational arguments characterize legitimate criticism and do not attack individual honor. This study emphasizes the importance of digital language ethics and public legal awareness in the expression of opinions politely and responsibly.